Seen and heard in Mexico : children and revolutionary cultural nationalism - Albarrán, Elena Jackson (Mexican experience., 2014)
An examination of the Mexican government's use of children to advance their state-formation goals following the Mexican Revolution, and the experience of children during this campaign.